IMPROVING THE TREATMENT METHODS FOR JUVENILE UTERINE BLEEDING - Nurullayeva Yoqutjon Egamberdi qizi; Yusupova Mehribon Otaxonovna (Web of Journals Publishing, 2025)
Juvenile uterine bleeding (JUB) is a common form of anovulatory bleeding in adolescent girls, occurring as a result of hormonal imbalance during the maturation phase of the reproductive system. This article analyzes existing approaches by evaluating the etiology, clinical signs, and modern treatment methods of JUB, as well as exploring ways to improve treatment based on an individualized approach and multidisciplinary medical care.
Keywords: Juvenile bleeding, adolescents, hormonal imbalance, treatment, reproductive health.